1996
DOI: 10.1002/(sici)1096-9861(19960513)368:4<487::aid-cne2>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Organisation of the cerebellar nucleus of the dogfish,Scyliorhinus canicula L.: A light microscopic, immunocytochemical, and ultrastructural study

Abstract: Elasmobranchs possess a well-developed cerebellum with an associated cerebellar nucleus. To determine whether the organization of this nucleus is comparable with that of the deep cerebellar nuclei of mammals, we studied the dogfish cerebellar nucleus with light microscopic methods (Nissl stain, Golgi method, reduced silver stain, NADPH-diaphorase histochemistry and immunocytochemistry) and with electron microscopy. We found the dogfish cerebellar nucleus to consist of about 1,050 large neurons, the ratio of Pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 55 publications
0
22
0
1
Order By: Relevance
“…Our results reveal that cerebellar efferent neurons are concentrated in three granular‐layer regions occupying a peripheral position in the three main parts of the cerebellum: the valvula, corpus, and auricles. In these locations they do not form an organized cerebellar nucleus, like that found in elasmobranchs (Paul and Roberts, 1984; Alvarez‐Otero et al, 1996). The efferent neurons of the teleost cerebellum are eurydendroid cells (Pouwels, 1978; Finger, 1978b; Meek et al, 1986b; Murakami and Morita, 1987; Torres et al, 1992; Díaz‐Regueira and Anadón, 2000), often located just below the Purkinje cell layer, unlike the cerebellar efferent cells of sturgeon.…”
Section: Discussionmentioning
confidence: 70%
“…Our results reveal that cerebellar efferent neurons are concentrated in three granular‐layer regions occupying a peripheral position in the three main parts of the cerebellum: the valvula, corpus, and auricles. In these locations they do not form an organized cerebellar nucleus, like that found in elasmobranchs (Paul and Roberts, 1984; Alvarez‐Otero et al, 1996). The efferent neurons of the teleost cerebellum are eurydendroid cells (Pouwels, 1978; Finger, 1978b; Meek et al, 1986b; Murakami and Morita, 1987; Torres et al, 1992; Díaz‐Regueira and Anadón, 2000), often located just below the Purkinje cell layer, unlike the cerebellar efferent cells of sturgeon.…”
Section: Discussionmentioning
confidence: 70%
“…This study has identified a putative nitrergic cerebellar nucleus in cladistians according to its localization. Elasmobranches possess a well‐developed cerebellar nucleus positive for the NADPH‐d reaction (Álvarez‐Otero et al, ; Pose‐Mendez et al, ). Although no similar group has been described for teleosts, it was identified in some species of amphibians (Lázár and Losonczy, ; Huynh and Boyd, ), reptiles (Brüning et al, ; Smeets et al, ), birds (Cozzi et al, ; Atoji et al, ), and mammals (Vincent and Kimura, ), representing a variable feature that appears several times in evolution.…”
Section: Discussionmentioning
confidence: 99%
“…The DCN projection neurons receive afferents from PCs and send their efferent axons outside the cerebellum, including the red nuclei (Ebbesson & Campbell ; Paul & Roberts ; Alvarez‐Otero et al . ; Butler & Hodos ). These features indicate that the cartilaginous fish have cerebellar neural circuits similar to those of amniotes, although there are some differences between them.…”
Section: Diversity In Cerebellum Structurementioning
confidence: 99%
“…The cartilaginous fish cerebellum contains DCNs that include projection neurons and interneurons, located in the cerebellar peduncles that connect the cerebellum with other regions of the CNS. The DCN projection neurons receive afferents from PCs and send their efferent axons outside the cerebellum, including the red nuclei (Ebbesson & Campbell 1973;Paul & Roberts 1984;Alvarez-Otero et al 1996;Butler & Hodos 2005). These features indicate that the cartilaginous fish have cerebellar neural circuits similar to those of amniotes, although there are some differences between them.…”
Section: Cartilaginous Fishesmentioning
confidence: 99%
See 1 more Smart Citation